Pulse Width Modulation (PWM) controlled Voltage Source Inverter (VSI) for active filtering applications / Norhaniza Muhamad - Muhamad, Norhaniza (2001)
Power conversion deals with the process of converting electric power from one form to another. The power electronic apparatus performing the power conversion are called power converters. The power conversion is achieved using power semiconductor devices, which are used as switches. The power devices used are SCRs (or thyristor), triacs, power transistors, power MOSFETs, I GB Ts, and MCTs (MOScontrolled thyristors). The power converters are generally classified as; AC-DC converters (phase-controlled converters), Direct AC-AC converters (cycloconverters), DC-AC converters (inverters), DC-DC converters (choppers, buck and boost converters). However the circuit that changes the characteristic of electrical energy from one form to another are tend to generate harmonic distortion in the supply source. Therefore the solution of this problem by using the active filters within the converter (rectifier-boost) or active filter external the converter (APF). This paper presents a study of a voltage source inverter (VSI) suitable for use in active filtering applications. The model of the active filtering 1s simulated with the help of MATLAB/SIMULINK package. It employing sinusoidal pulse width modulation (SPWM) technique-is given for evaluation and validation of the proposed concept.